Pengaruh Reward Dan Punishment Terhadap Disiplin Kerja Karyawan Pada PT. Pos Indonesia (Persero) Tasikmalaya - Dina Febrianti; Budhi Wahyu Fitriadi; Mila Karmila (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The purpose of this study is to determine and analyze the influence of reward, punishment and employee discipline at PT. Pos Indonesia (Persero) Tasikmalaya. The research method used is a survey method with a quantitative approach, the data obtained directly through questionnaires to 45 respondents taken from employees of PT. Pos Indonesia (Persero) Tasikmalaya. Sampling used saturated sampling technique and the analytical method used in this study was multiple linear regression analysis using SPSS 25 software. The test results showed that rewards partially had a significant effect on work discipline and punishment partially had a significant effect on work discipline. Simultaneously reward and punishment have a significant effect on employee discipline at PT. Pos Indonesia (Persero) Tasikmalaya.